Association between high-dose methotrexate-induced toxicity and polymorphisms within methotrexate pathway genes in acute lymphoblastic leukemia - Xu, Meng; Wu, Shuangshuang; Wang, Yue; Zhao, Yundong; Wang, Ximin; Wei, Changhong; Liu, Xueying; Hao, Feng; Hu, Cheng (Frontiers in Pharmacology, 2022)
Abstract: Methotrexate (MTX) is a folic acid antagonist, the mechanism of action is to inhibit DNA synthesis, repair and cell proliferation by decreasing the activities of several folate-dependent enzymes. It is widely used as a chemotherapy drug for children and adults with malignant tumors. High-dose methotrexate (HD-MTX) is an effective treatment for extramedullary infiltration and systemic consolidation in children with acute lymphoblastic leukemia (ALL). However, significant toxicity results in most patients treated with HD-MTX, which limits its use. HD-MTX-induced toxicity is heterogeneous, and this heterogeneity may be related to gene polymorphisms in related enzymes of the MTX intracellular metabolic pathway. To gain a deeper understanding of the differences in toxicity induced by HD-MTX in individuals, the present review examines the correlation between HD-MTX-induced toxicity and the gene polymorphisms of related enzymes in the MTX metabolic pathway in ALL. In this review, we conclude that only the association of SLCO1B1 and ARID5B gene polymorphisms with plasma levels of MTX and MTX-related toxicity is clearly described. These results suggest that SLCO1B1 and ARID5B gene polymorphisms should be evaluated before HD-MTX treatment. In addition, considering factors such as age and race, the other exact predictor of MTX induced toxicity in ALL needs to be further determined.